Ordinary and Extraordinary in Contemporary Art: Toward the Problem of Legitimizing the Unique and Reproducible in the Philosophy of Culture - Fradkinа, Natalya; Alimova, Viktoriia (Вісник гуманітарних наук, 2026)
The article is devoted to the analysis of the opposition of the ordinary and extraordinary in contemporary art through the prism of the philosophy of culture and the problem of legitimizing the artistic gesture. The purpose of the study is a philosophical and anthropological analysis of the opposition of the ordinary and extraordinary in contemporary art. Methods: hermeneutics, philosophical and anthropological and art historical analysis. Based on the material of the work of the Argentine artist Ides Kilen, Berlin museums and Ukrainian artists, the phenomenon of recognition, autonomy of the creative process, as well as the special status of a unique work in the conditions of reproducibility are considered. The thesis about the transformation of the criteria of artistic value in the era of digitalization and postmodernity is substantiated. Scientific results 1. The ordinary in the conditions of contemporary art is a structural condition of the extraordinary. 2. Uniqueness is transformed from a property into an effect. 3. Legitimation is contingent and event-based. 4. Ires Kilen (duration and bodily practice), Hamlet Zinkіvski (existential gesture) and the Berlin scene (institutionalization and hybrid generation) represent three models of contemporary art. In the digital age, art exists as a mode of circulation. Conclusions. In contemporary art, uniqueness is no longer tied to the object, and institutions perform the function of a «translator», therefore reproducibility does not destroy value. The shift in the ontology of art from the object of art to its procedural feature, which, in turn, depends on the context and network factor, is explored, which establishes new criteria for artistic value and legitimation. Therefore, in contemporary culture, the extraordinary is not an exception, but a way of organizing experience in different modes of reality. In Ires Kilen, the extraordinary is time and body, in Zinkіvskiy’s Hamlet the extraordinary is the everyday, in military Kharkiv the extraordinary acts as the limit of life, in Berlin the extraordinary as an institution and an algorithm. Uniqueness in the contemporary artistic situation is ensured by a set of spatio-temporal characteristics and methods of legitimation. Adding the military Ukrainian context radically strengthens the main thesis of our study, when in contemporary art the extraordinary is no longer an exception, it is a function of the limit situation, where life itself becomes an artistic gesture.